THE EFFECT OF WORKING CAPITAL TURNOVER AND RECEIVABLES TURNOVER OF RETURN ON EQUITY: A CASE STUDY FORM COOPERATIVE - Yamin, Muhammad; Pratiwi, Aliah (Univesitas Muhammadiyah Malang, 2020)
The research aims to determine the influence of working capital turnover, receivables turnover on return on equity (ROE) at Koperasi Pegawai Negeri (KPN)